Autonomous Robot Navigation in Human-Centered Environments Based on 3D Data Fusion. (25th February 2007) - Steinhaus Steinhaus, Peter Peter; Strand Strand, Marcus Marcus; Dillmann Dillmann, Rüdiger Rüdiger
Abstract : Efficient navigation of mobile platforms in dynamic human-centered environments is still an open research topic. We have already proposed an architecture (MEPHISTO) for a navigation system that is able to fulfill the main requirements of efficient navigation: fast and reliable sensor processing, extensive global world modeling, and distributed path planning. Our architecture uses a distributed system of sensor processing, world modeling, and path planning units. In this arcticle, we present implemented methods in the context of data fusion algorithms for 3D world modeling and real-time path planning. We also show results of the prototypic application of the system at the museum ZKM (center for art and media) in Karlsruhe.